Interventions for Cognitive Deficits in Breast Cancer Survivors Treated With Chemotherapy. Issue 1 (January 2017) - Vance, David E.; Frank, Jennifer Sandson; Bail, Jennifer; Triebel, Kristen L.; Niccolai, Lindsay M.; Gerstenecker, Adam; Meneses, Karen
Abstract : Background: Cognitive deficits are distressing adverse effects of chemotherapy that have a negative effect on quality of life in breast cancer survivors (BCSs). Cognitive deficits in cancer survivors are a top research and clinical practice priority. Objective: The aims of this study were to describe cognitive deficits that occur after chemotherapy, describe deficits in BCSs treated with chemotherapy within a framework of cognitive reserve and neuroplasticity, and discuss cognitive interventions (ie, cognitive training interventions, compensatory strategies with cognitive training interventions, pharmacological interventions, and complementary and integrative medicine interventions). Methods: PubMed search yielded 21 intervention studies of cognitive deficits in BCSs. Results: Cognitive training interventions and compensatory strategies with cognitive training resulted in improvement of cognitive deficits. Methylphenidate did not result in cognitive improvement. Modafinil showed improvement in attention. Some complementary and integrative medicine interventions are promising. Conclusions: Cognitive training has been most beneficial. Effectiveness of pharmacologic and complementary and integrative medicine interventions has not yet been established. Implications for Practice: While limited evidence is available to guide clinical management of cognitive deficits in BCSs, validating patients' symptom experience and evaluating co-occurring symptom clusters such as fatigue, sleep, and depression, are suggested.